Background
Lithium tantalate (LiTaO)3(ii) a LT) single crystal, which has piezoelectricity, is used as a piezoelectric substrate of a surface acoustic wave device. On the other hand, lithium tantalate single crystals are also pyroelectric, and change in temperature causes surface charge. Although such pyroelectricity is present when used as a sensor, it is problematic when lithium tantalate crystals are used as a piezoelectric substrate of a surface acoustic wave device.
For example, when the piezoelectric substrate is charged due to a temperature change, electrostatic discharge occurs in the piezoelectric substrate, which causes cracking and breaking. Further, the electrodes formed on the surface of the piezoelectric substrate may be short-circuited by static electricity.
Therefore, for the purpose of suppressing the electrification of the lithium tantalate substrate, a method of reducing the lithium tantalate substrate at a temperature equal to or lower than the curie temperature is considered to be widely used (see patent documents 1 to 5 and non-patent document 1).
For example, patent document 1 describes a method of performing a heat treatment in a reducing atmosphere together with a metal vapor, and patent document 2 describes a method of performing a heat treatment by bringing a reduction-treated substance into contact with the metal vapor at a curie temperature or higher in a reducing atmosphere. In addition, in patent documents 3 and 4, Al and Al are embedded2O3The method of heat-treating the mixed powder of (1). Thus, the volume resistivity of the lithium tantalate substrate subjected to such reduction treatment was 1 × 1012Omega cm is less than full, so that the pyroelectricity can be effectively inhibited.
It is also known that the lithium tantalate substrate subjected to the reduction treatment is blackened. The general lithium tantalate single crystal substrate has a light transmittance of about 70 to 80% at a wavelength of 365nm, and the lithium tantalate single crystal substrate subjected to the reduction treatment has a light transmittance of about 50 to 60% at a wavelength of 365nm, and such a light transmittance suppression is advantageous in the photolithography step in the production of the surface acoustic wave device.
On the other hand, in this lithium tantalate single crystal substrate, iron element may be added as described in patent documents 6 and 7, for example. Then, when the lithium tantalate single crystal substrate with the iron element added thereto is subjected to reduction treatment, the light transmittance is further suppressed as compared with the case where a normal lithium tantalate single crystal substrate is subjected to original treatment. The lithium tantalate single crystal substrate with the iron element added thereto had a light transmittance at 365nm of about 50%, but when this was subjected to reduction treatment, the light transmittance at 365nm became about 30%.
Documents of the prior art
Patent document
Patent document 1, Japanese laid-open patent application No. 2004-035396
Patent document 2WO 2004/079061
Japanese patent application laid-open No. 2005-119906
Japanese patent application laid-open No. 2005-119908
Japanese patent application laid-open No. 2005-314137 (patent document 5)
Japanese patent application laid-open No. 2004-254114
Patent document 7WO 2007/046176
Non-patent document
Non-patent document 1Yan Tao et al, "Formation mechanisms of Black LiTaO3Single crystals chemical reduction", "J.Appl.Crystal.44 (2011), 158-
However, as a method for reduction treatment of a lithium tantalate single crystal substrate, a method using an alkali metal compound is known. For example, patent document 5 describes a method of performing heat treatment under reduced pressure together with an alkali metal compound. Non-patent document 1 describes reacting Fe and Li in a nitrogen atmosphere2CO3The method of heat-treating the mixed powders together.
However, such a method of reducing a lithium tantalate single crystal substrate using an alkali metal compound has been found to have a problem. The present inventors have conducted a reproduction experiment for the method described in patent document 5, but could not perform the reduction treatment satisfactory for lithium tantalate single crystal substrates and could not suppress the pyroelectricity. Further, even if the reduction treatment is performed according to the method described in patent document 5, the pressure reduction step is necessary, and therefore, the productivity is poor.
In addition, the present inventors have also conducted a reproduction experiment with respect to the method described in non-patent document 1, and have been able to perform reduction treatment of a lithium tantalate single crystal substrate, but the degree of progress of reduction is insufficient, the surface of the substrate has irregularities, and the uniformity in the in-plane direction of the substrate is poor.
Accordingly, 1 object of the present invention is to provide a method for obtaining a high homogeneity and a high volume resistivity of 1X 10 without a pressure reduction step10Omega cm or more, 1X 1012A novel method for producing a lithium tantalate single crystal substrate having a width of not more than Ω & cm by reduction treatment.
In the photolithography step for producing the surface acoustic wave device, the lithium tantalate substrate preferably has a low transmittance of exposure light so that a fine and accurate pattern can be formed. In general, in photolithography, g-line (436nm), i-line (365nm), KrF excimer laser (248nm), or ArF excimer laser (193nm) from a mercury lamp is used as exposure light. In particular, in recent years, miniaturization is advancing, and exposure light having a wavelength shorter than that of i-line is often used.
Therefore, the lithium tantalate single crystal substrate added with iron element has a light transmittance at 365nm of about 30% as a result of reduction treatment, and is lower than the lithium tantalate single crystal substrate without added iron element in light transmittance at 365nm, which is advantageous in the photolithography step. In general, the light transmittance of the lithium tantalate single crystal substrate tends to be lower toward the short wavelength side and higher toward the long wavelength side.
On the other hand, the lithium tantalate single crystal substrate in which the light transmittance on the short wavelength side is low by the addition of the iron element or the reduction treatment also has a low light transmittance on the long wavelength side. It was confirmed that the light transmittance at a wavelength of 485nm was less than 50% in the lithium tantalate single crystal substrate in which the light transmittance at a wavelength of 365nm was 30% or less, due to the addition of the iron element and the reduction treatment.
The inventors of the present invention tested the reduction treatment of the lithium tantalate single crystal substrate with iron added by the method described in patent document 2, and confirmed that the transmittance at a wavelength of 365nm was 30% or less and the transmittance at a wavelength of 485nm was less than 50%.
However, in recent years, in a surface acoustic wave device, comb-shaped electrodes and the like are formed, and a functional substrate having a function as an element and a sealing substrate provided for protection of an electrode portion and the like are made of the same material, and in this case, since the material properties are the same, the surface acoustic wave device substrate and the sealing substrate are well integrated, and the workability and stability are excellent, and the number of cases where a material used as a functional substrate is used as a sealing material has increased.
However, in such a case, the light transmittance on the long wavelength side is low, and the workability of manufacturing the surface acoustic wave device may be deteriorated. When the functional substrate and the package substrate are integrated, an adjustment operation by a laser becomes necessary, and in this case, the adjustment operation is difficult if the light transmittance at the wavelength of the adjustment laser of the package substrate is low.
Therefore, the light transmittance of the lithium tantalate single crystal substrate is preferably lower on the shorter wavelength side than the exposure light used in the photolithography step, and is preferably as high as possible in a region having a longer wavelength than the exposure light used in the photolithography step.
Accordingly, the 2 nd object of the present invention is to provide a method for producing a lithium tantalate substrate having a light transmittance at a wavelength of 365nm of 30% or less and a light transmittance at a wavelength of 485nm of 50% or more, which can be favorably used as a functional substrate for a surface acoustic wave device and also as a package substrate.
Detailed Description
Hereinafter, an embodiment of the present invention will be described in detail, but the present invention is not limited thereto.
The invention is a method of making a polymer having a volume resistivity of 1 x 1010Omega cm or more, 1X 1012A method for producing a lithium tantalate substrate having a light transmittance at a wavelength of 365nm of 30% or less and a light transmittance at a wavelength of 485nm of 50% or more, in addition to the properties of not satisfying Ω · cm. In this production, first, a volume resistivity of 1 × 10 was prepared12A lithium tantalate single crystal substrate having a single domain structure and not less than Ω · cm. Such a lithium tantalate single crystal substrate is obtained by, for example, growing a lithium tantalate single crystal by the czochralski single crystal growth method, and processing the substrate shape while polarizing the obtained bulk.
In the first step of the heat treatment, the prepared lithium tantalate single crystal substrate is heat-treated at a temperature of 400 ℃ or higher and Curie temperature or lower in a hydrogen atmosphere at normal pressure. This is because, if the heat treatment is performed at a temperature lower than 400 ℃, the reduction does not proceed sufficiently, and if the heat treatment is performed at a temperature higher than the curie temperature, the structure tends to be a multi-domain structure. In this case, the flow rate of hydrogen is preferably 3l/min or more, more preferably 6l/min or more, so that fresh hydrogen is always present.
In the first step, the lithium tantalate single crystal substrate having a multi-domain structure, which has been heat-treated at a temperature equal to or higher than the curie temperature in a reducing gas atmosphere of hydrogen, nitrogen, or the like, is preferably brought into contact with the prepared lithium tantalate single crystal substrate and heat-treated.
In this case, it is preferable that the lithium tantalate single crystal substrates having a multi-domain structure heat-treated at a temperature equal to or higher than the curie temperature in a reducing atmosphere are alternately arranged so as to be in contact with both the front and back surfaces of the prepared lithium tantalate single crystal substrate. Thus, the uniformity in the thickness direction of the substrate is improved.
Further, as a second step of the heat treatment, the substrate after the first step is subjected to heat treatment together with lithium carbonate at a temperature of 400 ℃ or higher and curie temperature or lower under normal pressure in a hydrogen or nitrogen atmosphere. The second step is also not preferable to be carried out at a temperature of 400 ℃ or more than the Curie temperature for the same reason as in the case of the first step. In this case, the flow rate of hydrogen or nitrogen is preferably 3l/min or more, more preferably 6l/min or more, so that fresh gas may be always present,
in the second step, either hydrogen or nitrogen may be used. Nitrogen, safety, cost of equipment and the like can be suppressed, and is preferable. On the other hand, the reduction action of hydrogen gas is strong, and the permeability and volume resistivity of the processed substrate tend to be low.
Here, the lithium carbonate used in the second step is considered to partially decompose at a temperature of 948K or less to produce lithium oxide, carbon dioxide, and carbon monoxide, which is assumed to be Ta5+Reduction to Ta4+. Here, as the catalyst, a small amount of iron or the like may be present in addition to lithium carbonate. Iron decomposes the generated carbon dioxide into carbon monoxide, and thus promotes the reduction of lithium tantalate. If iron is mixed into lithium carbonate, the reduction is promoted as compared with the case of reducing the lithium carbonate alone, but when the lithium carbonate and iron are heat-treated together, the surface of the substrate is mottled, and therefore, it is preferable to use only lithium carbonate.
In the second step, the substrate treated in the first step is preferably embedded in the lithium carbonate powder, and the lithium carbonate powder is preferably embedded so as to be in contact with both the front and back surfaces of the substrate. In the case of processing a plurality of substrates at the same time, the lithium carbonate powder may be present between the substrates.
After the first and second steps, the substrate is polished, if necessary, to obtain a substrate having a volume resistivity of 1 × 1010Omega cm or more, 1X 1012A homogeneous lithium tantalate single crystal substrate having a width of Ω · cm less. Such as a volume resistivity ratio of 1X 1010The low Ω · cm causes deterioration of piezoelectric characteristics and may cause dielectric breakdown. On the other hand, e.g. volume resistivity of 1X 1012Omega · cm or more, and is easily charged, resulting in short-circuiting of electrodes and the like. Therefore, it is necessary to control within this numerical range. By controlling the volume resistivity in this manner, charging due to pyroelectricity can be suppressed, and thus, breakage and breakage of the substrate and short-circuiting of the electrodes can be prevented.
The method for producing a lithium tantalate single crystal substrate of the present invention is suitable for a lithium tantalate single crystal substrate containing an additive element, and is particularly suitable for a lithium tantalate single crystal substrate containing an iron element. By adding iron to the lithium tantalate single crystal, the light transmittance at 365nm can be suppressed to 30% or less, and the light transmittance at 485nm can be maintained to 50% or more. In this case, the light transmittance at 365nm wavelength can be effectively suppressed if the iron content is 50ppm to 200ppm by weight, but if it is outside the range of 50ppm to 200ppm, the light transmittance at 365nm wavelength cannot be sufficiently suppressed, the light transmittance at 485nm wavelength is difficult to be maintained at 50% or more, and various characteristics such as piezoelectric characteristics are deteriorated, which is not preferable.
Although not limited to the method of adding iron to the lithium tantalate single crystal, in general, when growing the lithium tantalate single crystal by the Czochralski single crystal growth method, if iron oxide (Fe) is added to the raw material melt2O3) And the like. When the reduction treatment method of the present invention is applied to a lithium tantalate single-crystal substrate containing iron as an additive element, a lithium tantalate single-crystal substrate having a volume resistivity of 1X 10 can be obtained10Omega cm or more, 1X 1012A homogeneous lithium tantalate single crystal substrate having a width of Ω · cm less.
When the reduction treatment method of the present invention is applied to a lithium tantalate single crystal substrate whose additive element is iron, the light transmittance at a wavelength of 365nm can be made 30% or less. Thus, the optical transmittance at 365nm is more preferably 25% or less, which is advantageous for the photolithography step using a light source having a shorter wavelength than the i-line (365nm wavelength).
Further, when the reduction treatment method of the present invention is applied to a lithium tantalate single crystal substrate in which iron is used as an additive element, the transmittance at a wavelength of 485nm can be made 50% or more. As described above, when the lithium tantalate single crystal substrate is used as a sealing material, the adjustment work of the functional substrate becomes easy.
Examples
Example 1
In example 1, first, a lithium tantalate single crystal was grown by the czochralski single crystal growth method, the obtained bulk was polarized and monodomain-formed, and then, the bulk was sliced to obtain a plurality of substrates (raw material substrates). Further, a normal lithium tantalate single crystal substrate was exposed to hydrogen gas at 1050 ℃, and a multi-domain substrate was prepared.
Then, as a first step of the heat treatment, the volume resistivity of the single domain was set to 4.5 × 1014The lithium tantalate single crystal substrate of Ω · cm and the lithium tantalate single crystal substrate in which the regions were formed were brought into contact, and heat treatment was performed at a temperature of 570 ℃ for 8 hours under normal pressure and in an atmosphere of 100% hydrogen.
Further, as a second step of the heat treatment, the raw material substrate after the first step is taken out and embedded in lithium carbonate powder. Thereafter, the substrate embedded in the lithium carbonate powder was subjected to a heat treatment at 530 ℃ for 8 hours under normal pressure and in an atmosphere of 100% hydrogen.
Further, after polishing both surfaces of the substrate obtained by the first and second steps to obtain a lithium tantalate single crystal substrate having a thickness of 0.2mm, the volume resistivity of the lithium tantalate single crystal substrate was measured to be 2.0X 1011Omega cm. Further, when the light transmittances were measured at 365nm and 485nm, the light transmittance at 365nm was 60% and the light transmittance at 485nm was 65%.
Example 2
In example 2, first, a lithium tantalate single crystal containing 100ppm by weight of iron element was polarized in a bulk obtained by the czochralski single crystal growth method, and the bulk was sliced to obtain a plurality of substrates.
Then, these volume resistivities were set to 4.5X 1014The substrate of Ω · cm was subjected to a heat treatment at a temperature of 570 ℃ for 8 hours under normal pressure and in a hydrogen 100% atmosphere as a first step of the heat treatment.
Further, as a second step of the heat treatment, the substrate after the first step is taken out and embedded in lithium carbonate powder. Thereafter, the substrate embedded in the lithium carbonate powder was subjected to a heat treatment at 530 ℃ for 8 hours under normal pressure and in a hydrogen 100% atmosphere.
Further, after both surfaces of the substrate after the first and second steps were polished to obtain a lithium tantalate single crystal substrate having a thickness of 0.2mm, light transmittances at 365nm and 485nm were measured for the iron-containing lithium tantalate single crystal substrate, and as a result, the light transmittance at 365nm was 25%, and the light transmittance at 485nm was 58%. The volume resistivity of the obtained substrate was measured, and found to be 1.0 × 1011Ω·cm。
Example 3
In example 3, first, a lithium tantalate single crystal containing 100ppm by weight of iron element was grown by the czochralski single crystal growth method, and the obtained bulk was single-regionalized by polarization (poling), and then cut into a plurality of substrates (raw material substrates). Further, a normal lithium tantalate single crystal substrate was exposed to hydrogen gas at 1050 ℃ to prepare a multizoned substrate.
Then, as a first step of the heat treatment, the volume resistivity of the steel sheet was changed to 4.5X 10 by making the steel sheet have a monodomain structure containing 100ppm of iron element14The Ω · cm lithium tantalate single crystal substrate and the multizoned lithium tantalate single crystal substrate were brought into contact, and heat treatment was performed at a temperature of 570 ℃ for 8 hours under normal pressure and in a hydrogen 100% atmosphere.
Further, the second step of the heat treatment and the polishing step were carried out under the same conditions as in example 1, and after a lithium tantalate single crystal substrate having a thickness of 0.2mm was obtained, the iron-containing element lithium tantalate single crystal substrate was measured for light transmittance at a wavelength of 365nm and light transmittance at a wavelength of 485nm, and it was found that the light transmittance at a wavelength of 365nm was 20% and the light transmittance at a wavelength of 485nm was measuredThe light transmittance at nm was 55%. The volume resistivity of the obtained substrate was measured, and found to be 5.5 × 1010Ω·cm。
Comparative example
Comparative example 1
In comparative example 1, first, a lithium tantalate single crystal was grown by the czochralski single crystal growth method, and the obtained bulk was polarized and monodomain-ized, and then, the bulk was sliced to obtain a plurality of substrates (raw material substrates).
Further, the volume resistivity was set to 4.5X 1014Omega cm substrate is embedded with mixed powder of iron and lithium carbonate (Fe: Li)2CO35: 100 byglass), the substrate embedded in the mixed powder was subjected to a heat treatment at 540 ℃ for 6 hours under normal pressure and in a nitrogen 100% atmosphere.
Further, after polishing both surfaces of the heat-treated substrate to obtain a lithium tantalate single crystal substrate having a thickness of 0.2mm, the volume resistivity of the lithium tantalate single crystal substrate was measured to find that the value was 7.3X 1011Ω·cm~2.3×1012Omega cm. The substrate surface had color unevenness, and the uniformity in the in-plane direction of the substrate was poor.
In comparative example 1, the reduction treatment of the lithium tantalate single crystal substrate was performed only 1 time, and the maximum value of the volume resistivity was 2.3 × 10 for sufficient reduction12Ω · cm, high, and poor homogeneity in the in-plane direction of the substrate. Further, the lithium carbonate and iron were heat-treated in the mixed powder, and color unevenness occurred on the substrate surface.
Comparative example 2
In comparative example 2, first, a lithium tantalate single crystal was grown by the czochralski single crystal growth method, and the obtained bulk was subjected to polarization treatment and then sliced into a plurality of substrates.
Then, the volume resistivity was set to 4.5X 1014Both sides of the Ω · cm substrate were polished to obtain a lithium tantalate single crystal substrate having a thickness of 0.2mm, and then light transmittances at 365nm and 485nm were measured for the lithium tantalate single crystal substrate, and it was found that the light transmittance at 365nm was72 percent and the light transmittance of 485nm wavelength is 75 percent. The volume resistivity of the obtained substrate was measured, and it was 4.5X 1014Ω·cm。
In comparative example 2, since the reduction treatment of the lithium tantalate single crystal substrate was not performed, the light transmittance at a wavelength of 365nm was as high as 72%, and the volume resistivity was as high as 4.5X 1014Omega. cm, satisfactory results could not be obtained.
Comparative example 3
In comparative example 3, lithium tantalate single crystal containing 100ppm by weight of iron element was first grown by the czochralski single crystal growth method, and the obtained bulk was polarized and sliced to obtain a plurality of substrates.
Then, the volume resistivity was set to 5.0X 1013After both surfaces of the Ω · cm substrate were polished to obtain a lithium tantalate single crystal substrate having a thickness of 0.2mm, the lithium tantalate single crystal substrate containing this iron element was subjected to measurement of light transmittance at 365nm and 485nm, and it was found that the light transmittance at 365nm was 50% and the light transmittance at 485nm was 65%. The volume resistivity of the obtained substrate was measured and found to be 5.0X 1013Ω·cm。
In comparative example 3, since the lithium tantalate single crystal substrate containing iron element was not subjected to the reduction treatment, the light transmittance at a wavelength of 365nm was 50%, which was high, and the volume resistivity was also 5.0X 1013Omega. cm, high, no satisfactory.
Comparative example 4
In comparative example 4, first, a lithium tantalate single crystal containing 100ppm by weight of iron element was grown by the czochralski single crystal growth method, and the obtained bulk was subjected to polarization treatment and then sliced to obtain a plurality of substrates. Further, a normal lithium tantalate single crystal substrate was exposed to hydrogen gas at 1050 ℃, and a multi-domain substrate was prepared.
Then, as a first step of the heat treatment, the volume resistivity of the polarized treated steel sheet was 5.0X 10 with 100ppm of iron-containing element13Contacting omega-cm lithium tantalate single crystal substrate with multizoned lithium tantalate single crystal substrateHeat treatment at 570 ℃ for 8 hours in a hydrogen 100% atmosphere under reduced pressure.
Further, as a second step of the heat treatment, the heat treatment is performed under the same treatment conditions as those in the first step.
Further, after both surfaces of the substrate after the first and second steps were polished to obtain a lithium tantalate single crystal substrate having a thickness of 0.2mm, light transmittances at 365nm and 485nm were measured for the iron element-containing lithium tantalate single crystal substrate, and it was found that the light transmittance at 365nm was 25%, and the light transmittance at 485nm was 45%. The volume resistivity of the obtained substrate was measured, and it was 1.0X 1011Ω·cm。
In comparative example 4, the lithium tantalate single crystal substrate containing iron element was subjected to reduction treatment, but in the second step, the raw material substrate after the first step was not heat-treated together with lithium carbonate, and the light transmittance at a wavelength of 485nm was 45% which was smaller than 50%, and satisfactory material was not obtained.